Redescription of Scolelepis tridentata (Southern, 1914) (Annelida: Spionidae), with description of a new species of Scolelepis from the Black Sea - Victor Surugiu (The European Zoological Journal, 2023)
AbstractThe spionid genus Scolelepis is commonly divided into the subgenera Scolelepis (s. str.) and Parascolelepis. In the Black Sea, two species ascribed to the subgenus Parascolelepis have been reported so far – Scolelepis tridentata and Scolelepis cantabra. Both species are quite rare and when found are usually difficult to identify because of their fragility. To ascertain the identity of specimens from the Black Sea, the type-series of S. tridentata and non-type specimens of S. cantabra were examined. The examination of specimens from the Black Sea identified as Scolelepis tridentata revealed that they differ from the nominal species in several characters. Therefore, they are described herein as Scolelepis bellani n. sp., a species that most closely resembles S. korsuni from Arctic waters. Also, the occurrence of S. cantabra in the Black Sea is confirmed.http://zoobank.org/urn:lsid:zoobank.org:pub:78FD82BA-084F-4213-A7A0-41C1EA6ACD44http://zoobank.org/urn:lsid:zoobank.org:act:FF4E2A3C-7607-4402-9F79-42399574CCC5